Reliability Allocation and Optimization Problem for Waste Treatment Plant (WTP) - Saad Abbas Abed; Mahmood S. Fiadh; Ahmed Hussein Ali (Genius Journals, 2022)
The issue of waste treatment is one of the topics that have a direct impact on the environment and human life. In previous studies the mathematical model of waste treatment has proven its importance for large-scale waste treatment plant (WTP). Little experience has been gained in mathematical modeling of waste treatment plant. In this study an optimal waste treatment plant system (WTPS) was identified, a non-linear programming model was applied to assign reliability to the system. The problem was formulated as a non-linear programming as the C.F is the target function (which depends on the reliability of the system) as well as the reliability of the waste treatment plant system as a constraint function. The (O.P) has been solved to allocate reliability requirements by using one of the optimization methods Cukoo Optimization Algorithm (C.O.A). Important results have been reached to allocate the reliability of each component of the system used in our study at appropriate costs, which may help researchers in the future to find better ways to solve the problem of optimal reliability of the aforementioned system above (i) The system used in this paper is (W. T. P) system with the C.F. (ii) The results obtained were by using the (C .O .A) to solve specific system (R.O.P).
Keywords: Reliability network; Reliability Optimization problem; Reliability allocation; Cukoo Algorithm